2021
DOI: 10.48550/arxiv.2105.07213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stationary Discounted and Ergodic Mean Field Games of Singular Control

Abstract: We study stationary mean field games with singular controls in which the representative player interacts with a long-time weighted average of the population through a discounted and an ergodic performance criterion. This class of games finds natural applications in the context of optimal productivity expansion in dynamic oligopolies. We prove existence and uniqueness of the mean field equilibria, which are completely characterized through nonlinear equations. Furthermore, we relate the mean field equilibria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…By employing, respectively, the connection to problems of optimal stopping and PDE methods, the structure of the mean-field equilibrium as well as its connection to Nash equilibria for the corresponding N -player stochastic differential games is derived. Finally, [16] and [15] study stationary MFGs, i.e. games in which the interaction comes through the stationary distribution of the population of players.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…By employing, respectively, the connection to problems of optimal stopping and PDE methods, the structure of the mean-field equilibrium as well as its connection to Nash equilibria for the corresponding N -player stochastic differential games is derived. Finally, [16] and [15] study stationary MFGs, i.e. games in which the interaction comes through the stationary distribution of the population of players.…”
Section: 2mentioning
confidence: 99%
“…games in which the interaction comes through the stationary distribution of the population of players. [15] considers ergodic and discounted performance criteria, and studies the relation across the corresponding equilibria; in [16] the representative player can employ two-sided controls in order to adjust a geometric dynamics and optimize a certain discounted payoff. It is worth noting that none of the previous contributions allows for the presence of common noise, which we can instead treat in our analysis.…”
Section: 2mentioning
confidence: 99%
“…In the stationary mean-field regime [31], [32], [35], the following additional assumptions are made: -Time homogeneous strategy: All IoT devices follow a time-homogeneous power allocation strategy 𝑝 𝑡 = 𝑝 : Ω → [0, 𝑃 𝑚𝑎𝑥 ].…”
Section: B Stationary Regimementioning
confidence: 99%
“…This approximation, however, is only significant if the associated approximation error is small. It has been shown that under appropriate conditions, the mean-field regime realizes an 𝜖-Nash equilibrium for the dynamic differential game, with 𝜖 converging to zero as the number of players goes to infinity [35].…”
Section: B Stationary Regimementioning
confidence: 99%
“…Both papers do not consider the vanishing discount approach which we do here. The recent paper [5] considers the vanishing discount approach, but in a continuous-time setting and for a game.…”
Section: Introductionmentioning
confidence: 99%